PELATIHAN DAN PENDAMPINGAN PENULISAN ARTIKEL ILMIAH DAN MANAGER REFERENCE BAGI GURU UPTD SMPN 2 METRO - Aria Septi Anggaira; Endah Wulantina (JPM: Jurnal Pengabdian Masyarakat, 2021)
Currently being a professional teacher is proven by the ability to write scientific papers as a condition for promotion and position. Unfortunately, in reality many teachers have not been able to write scientific papers, especially in the form of articles to be published in journals. Community service activities carried out by providing training and assistance in writing scientific articles for UPTD SMPN 2 Metro teachers. The purpose of this activity is to provide knowledge and skills about writing scientific articles with the output in the form of articles that are ready to be published. The method of implementing this service activity is the in-service training program, namely training and mentoring for teachers at SMPN 2 Metro. The results of the training and mentoring, there were 5 teachers out of 29 training participants who were able to make and ready for publication, and the others were still in the process of conducting research, which then the results of their research were written into scientific articles.